Spatiotemporal Patterns of Agricultural Drought in Sri Lanka: 1881–2010. (5th May 2015) - Gunda, Thushara; Hornberger, George M.; Gilligan, Jonathan M.
ABSTRACT: A spatiotemporal analysis of two well‐known agricultural drought indices, the Palmer Drought Severity Index (PDSI) and the Standardized Precipitation Index at a 9‐month scale (SPI‐9), is presented for Sri Lanka. The analysis was conducted based on monthly precipitation and temperature data from January 1881 to December 2010 using 13 stations distributed across the three climatic zones of the country. Principal component analysis shows that the first two principal components of PDSI and SPI‐9 are spatially comparable and could physically represent the two main monsoons. A wavelet analysis of these principal components' scores for both indices indicates a stronger association between the Northeastern monsoon and El‐Niño in recent decades. Correlation analysis with agricultural metrics suggests that different indices might be appropriate for each of the climatic zones in Sri Lanka. PDSI correlated best with the intermediate zone districts; SPI‐9 correlated best with the dry zone districts; but neither index correlated well with the wet zone districts.